Perijinan dan Tindak Pidana Terhadap Juru Parkir Liar di Kota Denpasar - Kadek Agus Mahendra Wijaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Permit is an agreement based on government regulations in certain circumstances as stipulated in the legislation. The formulation of the problem in this study is how is the regulation of parking permits in the city of Denpasar? and What are the legal sanctions for parking attendants if they do not have a permit? In this study, the author uses a normative research method with a statutory and conceptual approach. The results of the study to get a permit as a parking attendant are procedures and processes in order to get a permit as a parking interpreter in the city of Denpasar. Illegal parking attendants will receive the punishment obtained from the act of collecting illegal parking fees as a violation of the law. Parking permits in Denpasar City are clearly regulated in the Standard Operating Procedure for accepting parking attendants as contained in the Decree of the Board of Directors of the Regional Public Company Bhukti Praja Sewakadharma Denpasar City Number 1 of 2022 concerning Rules of Conduct and Behavior along with Sanctions for Parking Officers and Parking Attendants. The legal sanction obtained by the illegal judge is subject to Article 368 paragraph (1) of the Criminal Code.